A multicenter study comparing surgical outcomes and ultrasonographic evaluation of scarring after laparoscopic myomectomy with conventional versus barbed sutures. Issue 1 (31st March 2016) - Tinelli, Raffaele; Litta, Pietro; Angioni, Stefano; Bettocchi, Stefano; Fusco, Annarita; Leo, Livio; Landi, Stefano; Cicinelli, Ettore
Abstract: Objective: To compare clinical outcomes after laparoscopic myomectomy using traditional interrupted sutures (TIS) versus continuous barbed suture (CBS) for treatment of symptomatic uterine myomas. Methods: In a multicenter retrospective study, data were obtained for women with uterine myomas who underwent laparoscopic myomectomy at three centers between January 1, 2009 and January 31, 2015. Suturing of the uterine wall had been performed initially using TIS; CBS were used from January 31, 2012. Results: Overall, laparoscopic myomectomy was performed using CBS for 360 women and using TIS for another 360. The mean operative time was 52 ± 19 min using CBS and 67 ± 21 min using TIS groups ( P = 0.001). The mean blood loss was 135 ± 35 mL in the CBS group and 215 ± 55 mL in the TIS group ( P = 0.006). The mean decrease in hemoglobin was 1.2 ± 0.2 g/L in the CBS group and 1.2 ± 0.2 g/L in the TIS group ( P = 0.072). Conclusion: Laparoscopic myomectomy using CBS is a suitable alternative to TIS in the treatment of uterine myomas for women with up to three tumors.